Long-term outcomes in thoracic aortic surgery: 11 year single centre experience - Edward Staniforth; Iakovos Ttofi; Jasmina Ttofi; Vanitha Perinparajah; Rohit Vijjhalwar; Raman Uberoi; Ediri Sideso; Shirish Dubey; George Krasopoulos (Journal of Cardiothoracic Surgery, 2024)
Abstract Objectives Thoracic aortic aneurysms and dissections provide a complex surgical cohort termed thoracic aortic surgery. Regular follow-up at specialist clinics with cross-sectional imaging is recommended. Identifying risk factors that lead to re-operations as well as the requirement for and appropriate length of follow-up remain points of debate. Methods Patients undergoing thoracic aortic surgery performed at a single centre from January 2012 to December 2022 were retrospectively reviewed. The clinical information, operative details, histological reports, post-operative outcomes and follow up were collected from electronic patient records. Statistical analysis was performed using Microsoft Excel and R Studio. Results 409 patients met the inclusion criteria for the study with a median follow-up of 3.8 years (IQR 1.6–7.6). The prevalence of all cause re-operations was 10.8% (n = 44). The median time to re-operation was 1.8 years. 68% of the reoperations occurred within the first 5 years. Multi and univariate logistic regression identified young age, arteritis and/or aortitis as the main risk factors associated with increased risk of re-operation. Connective tissue disease and systemic inflammatory diseases approached but didn’t meet statistical significance. Bicuspid aortic valve pathology was associated with reduced risk of re-operation. Conclusions Patients undergoing thoracic aortic surgery have a high rate of re-operation. The first 5 years represent a high-risk period and follow-up with cross-sectional imaging during that time by specialist aortic services is essential. Patient with aortitis remain at high risk and should be treated by appropriate by specialist aortic services with subspecialty interest and expertise on treating patients with aortitis. Graphical Abstract